Cladocera Diversity in the Aquatic Habitats of Jammu District, (J&K) - Kotwal, Sanjay (International Journal of Scientific Research in Biological Sciences, 2020)
Cladocera occupy the primary consumer level in aquatic food chains and have a very vital role in stability and integrity of aquatic habitats. Therefore, knowledge of biodiversity of these organisms can be utilized in the management of aquatic habitats and for commercial aquaculture practices. The present study involved analysis of diversity and dynamics of these planktonic crustacea in Jammu district of the Union Territory of Jammu and Kashmir. This investigation recorded 15 species of cladocera belonging to 8 genera and 4 families from the study area. The percental contribution of different families demonstrated a typical trend where Daphniidae>Chydoridae>Moinidae>Macrothricidae. Habitat preference was also recorded in some cladocera.